Tourism and the Highlands: A cross-sectional study on trauma and orthopaedic service use by tourists in 2017. Issue 3 (June 2021) - Faulkner, Alastair; Harding, Thomas; Miller, Craig; Davies, Peter; McNair, Colin
Abstract: Background: NHS Highland covers a wide geographical region encompassing the Isle of Skye, and Ben Nevis. Tourism is a significant contributor to the local economy and in 2017 the Highlands welcomed 534, 000 visitors. Health services across the region treat tourists in addition to the local population. We investigated how many tourists accessed the Trauma and Orthopaedic (T&O) Department at Raigmore Hospital, Inverness. Methods: We conducted a cross-sectional study with data collected over one year (2017). The number of tourists referred to T&O including patient demographics, country of origin, type of injury and their clinical outcome were recorded. A freedom of information (FOI) request to NHS Highland was sought to investigate associated costs incurred by tourists. Results: 376 tourists accessed T&O services in 2017. Country of origin: 47 (12.5%) Scotland; 177 (47.1%) rest of UK; 74 (19.7%) EU; 45 (12.0%) non-EU. Highest referral month August (61), lowest referral month November (8). Injuries: 224 (59.6%) fracture; 62 (16.5%) soft tissue injury; 20 (5.3%) laceration. Commonest sites of injury were ankle, distal radius and finger. Outcomes: 28 (7.4%) Virtual clinic; 137 (36.4%) hospital admission; 193 (51.3%) advice to referring team and discharge; 13 (3.5%) direct discharge by T&O; 4 (1.1%) missing. No. of trauma cases booked: tourists 133 (9%), local population 1415 (91%). Conclusions: Tourists account for fewer than ten percent of the T&O surgical workload over one year with common injuries being fractures affecting the extremities. Seasonal variation was observed with more referrals occurring in the summer months. Just under half of tourists originated from outside the UK and EU. Health boards should consider increasing resources over the summer months to deal with expected increases in tourist numbers and should be able to recover the cost of treatment from the patient or their travel insurance companies directly at point of care. Highlights: More summer tourists use Highlands' trauma & orthopaedic services compared with winter. Fractures of the extremities including the wrist and ankle were the most common injuries. Almost 50% of tourists using NHS are ineligible for treatment costs under EU RHCA. The NHS is not being reimbursed fully for treating tourists in the Highlands.